Supply chain cost control using activity-based management - Kumar, Sameer; Zander, Matthew (Supply chain integration series, 2007)
Discusses the advantage that cost analysis and management can bring to companies within a supply chain. This book addresses strategies to evaluate the total cost inherent in a customer-supplier relationship, using total cost of ownership, activity-based costing, and activity-based management (ABM) for analyzing and controlling supply chain costs.